Situating moral disengagement: motivated reasoning in meat consumption and substitution - Graça, J. (2016)
This work advances towards an increased understanding of moral disengagement and individual differences in the maintenance of widespread and cherished harmful behaviors. Drawing on meat consumption and substitution as an opportunity to study the process of moral self-regulation in situ, it presents a measure of selective deactivation of moral self-regulatory processes when considering the impact of meat consumption (i.e. the Moral Disengagement in Meat Questionnaire — MDMQ). The MDMQ developed from four sequential studies following a mixed-methods approach. Two preliminary studies (40 and 410 participants, respectively) provided input to develop the construct and initial pool of items. Two additional studies (1016 and 318 participants, respectively) allowed the assessment of item selection, factor structure, reliability, convergent and concurrent validities, predictive ability, and measurement invariance. The MDMQ was associated with a variety of individual differences concerning moral self-regulation (i.e. propensity to morally disengage; moral identity; empathy; moral emotions) and endorsement of dominance ideologies (i.e. social dominance orientation; speciesism; human supremacy beliefs). In a sequential mediation model, frequency of meat consumption affected willingness towards meat substitution indirectly via meat attachment and moral disengagement. We offer an interpretation of moral disengagement as a motivated reasoning process which is triggered by loss aversion and dissonance avoidance.